2022
DOI: 10.1177/14771535221135226
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising innovative lighting interventions for suicide, trespass and risky behaviour on the railway

Abstract: Three behaviour types – suicide, trespass and risky behaviours, which can result in entry to railway tracks – present an ongoing challenge to the rail industry for fatality prevention. Many preventative interventions exist, operating at different stages in the timeline of a person’s decision to access the tracks to the point that they have entered and remain in the track area. However, there is little understanding of the impacts of interventions on the behaviours in question. This paper outlines the generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Trespasser profile and behaviour (Silla and Luoma, 2012) [43], (Silla and Luoma, 2009) [11], (Skladana et al, 2019) [40], (Pelletier, 1997) [13], (Patterson, 2004) [24], (Federal Railroad Administration, 2008) [30], (Davis et al, 1997) [56], (Matzopoulos et al, 2006) [71], (Havârneanu et al, 2016) [72], (Havârneanu et al, 2015) [16], (Hoekstra and Wegman, 2011) [73], (Waterson et al, 2015) [74], (DaSilva and Carroll, 2011) [75], (Department of transportation (FRA), 2011) [76], (Edwards, 1953) [77], (Cohen et al, 2003) [78], (Ricketts et al, 2010) [79], (Ricketts, 2015) [80], (Lobb et al, 2003) [81], (Hallewell et al, 2022) [82] 2. Signalization, technological and technical measures for trespassing prevention (Silla and Luoma, 2011) [83], (Federal Railroad Administration 2011) [84], (Waterson and Monk, 2014) [85], (Horton and Da Silva) [86], (Oh et al, 2022) [87], (Gao et al, 2021) [88], (Tang et al, 2023)…”
Section: Main Trespassing Categories Trespassing Sub-categories Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trespasser profile and behaviour (Silla and Luoma, 2012) [43], (Silla and Luoma, 2009) [11], (Skladana et al, 2019) [40], (Pelletier, 1997) [13], (Patterson, 2004) [24], (Federal Railroad Administration, 2008) [30], (Davis et al, 1997) [56], (Matzopoulos et al, 2006) [71], (Havârneanu et al, 2016) [72], (Havârneanu et al, 2015) [16], (Hoekstra and Wegman, 2011) [73], (Waterson et al, 2015) [74], (DaSilva and Carroll, 2011) [75], (Department of transportation (FRA), 2011) [76], (Edwards, 1953) [77], (Cohen et al, 2003) [78], (Ricketts et al, 2010) [79], (Ricketts, 2015) [80], (Lobb et al, 2003) [81], (Hallewell et al, 2022) [82] 2. Signalization, technological and technical measures for trespassing prevention (Silla and Luoma, 2011) [83], (Federal Railroad Administration 2011) [84], (Waterson and Monk, 2014) [85], (Horton and Da Silva) [86], (Oh et al, 2022) [87], (Gao et al, 2021) [88], (Tang et al, 2023)…”
Section: Main Trespassing Categories Trespassing Sub-categories Authorsmentioning
confidence: 99%
“…Enforcement measures are also very effective when combined with education, as shown in research conducted in Auckland, New Zealand [81], where education alone was not as effective in the reduction of railway trespassing. However, education on safety has been proven to change the mindset of people, which is why the railway stakeholders in one study suggested that education on the dangers of electrification is needed at schools (alongside "normal" trespassing education) [82].…”
Section: Educational Measuresmentioning
confidence: 99%
“…For instance, the use of unexpected sensory stimuli, such as colored light or sound effects, at suicide risk places like railway areas, has shown promise in breaking through the emotional daze which suicidal people are likely to experience prior to an attempt. 27 Therapists should proactively inquire about the means that suicidal patients may have access to, not only during a suicidal crisis but also during the intake process, as preparations (such as choice of suicide method) can occur years prior to an attempt. In treatment settings, clinicians could explore certain dates that hold special meaning and be mindful of the possible burden of these dates.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the use of unexpected sensory stimuli, such as colored light or sound effects, at suicide risk places like railway areas, has shown promise in breaking through the emotional daze which suicidal people are likely to experience prior to an attempt. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Similar findings are reported in a recent Swedish study, where mid-track fencing at a station reduced suicides there by 62.5%, although there were some concerns about substitution effects, whereby an increase was observed in nearby stations that functioned as a control group [ 18 ]. Promising new techniques, including advanced sensor surveillance [ 19 ], video monitoring [ 20 ] and the effect of lighting [ 21 , 22 ] have been subjected to theoretical examination and assessed in feasibility studies, but evidence for their effects on a larger scale remains limited.…”
Section: Introductionmentioning
confidence: 99%